2012
DOI: 10.1038/labinvest.2011.122
|View full text |Cite
|
Sign up to set email alerts
|

Early endothelial damage and increased colonic vascular permeability in the development of experimental ulcerative colitis in rats and mice

Abstract: The role of endothelial damage and increased vascular permeability (VP) in the pathogenesis of ulcerative colitis (UC) has not been investigated. We examined using functional, morphologic, and molecular biologic studies whether and to what extent the endothelial barrier dysfunction precedes enhanced epithelial permeability (EP) and the development of mucosal lesions during the early stages of experimental UC. We showed that in rats with iodoacetamide (IA)-induced UC increased colonic VP occurs early (ie, 2.6-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 46 publications
(53 reference statements)
2
45
0
Order By: Relevance
“…() reported that pharmacological inhibition of TRPV4 prevents LPS‐induced endothelial dysfunction and increase in mesenteric artery permeability in mouse mesenteric arteries. Endothelial damage increases colonic vascular permeability, contributing to the pathogenesis of experimental colitis in rats and mice (Tolstanova et al, ). In this study, we found that the TRPV4 channel was up‐regulated in mouse endothelial cells during inflammatory conditions and a TRPV4 agonist increased vascular permeability in the colon of mice with DSS‐induced colitis, which was abolished by i.v.…”
Section: Discussionmentioning
confidence: 99%
“…() reported that pharmacological inhibition of TRPV4 prevents LPS‐induced endothelial dysfunction and increase in mesenteric artery permeability in mouse mesenteric arteries. Endothelial damage increases colonic vascular permeability, contributing to the pathogenesis of experimental colitis in rats and mice (Tolstanova et al, ). In this study, we found that the TRPV4 channel was up‐regulated in mouse endothelial cells during inflammatory conditions and a TRPV4 agonist increased vascular permeability in the colon of mice with DSS‐induced colitis, which was abolished by i.v.…”
Section: Discussionmentioning
confidence: 99%
“…An increased vascular permeability has been described in the inflamed colon of different mouse and rat models of experimental colitis (20,236,338,340,346,352,491). The increased vascular permeability appears to precede the mucosal barrier failure that accompanies this condition (490). Since increased vascular permeability is a critical component of the angiogenic response, an effort has been made to link the two events in experimental colitis.…”
Section: Vascular Responses To Chronic Inflammationmentioning
confidence: 99%
“…32,33 In this report, we evaluated the impact of Mk2 homozygous deletion (Mk2 À / À ) and WIN55, an agonist of CB receptors, on the local and systemic inflammatory response in mice with DSS-induced colitis taking advantage of the availability of Mk2 À / À mice and the mouse colitis model. Our results confirm that uptake of 4% DSS in drinking water for 7 consecutive days causes colitis with Figure 3 Inflammatory cell counting in colonic specimens of mice with dextran sodium sulfate (DSS)-induced colitis.…”
Section: Mk2 Deficiency and Win55 Administration Decrease Lung Mpo Acmentioning
confidence: 99%